Feasibility of Probiotic Lactobacillus casei FNCC 0090 to Improve Growth and Immune Response of Catfish (Clarias gariepinus) toward Aeromonas hydrophila Infection - Aini, Nurul; Wahyuningsih, Sri Puji Astuti; Fatimah; Andriyono, Sapto; Do, Hoang Dang Khoa; Bachruddin, Muhammad (Bogor Agricultural University, Indonesia, 2025)
Aeromonas hydrophila can cause motile Aeromonas septicemia, leading to high mortality in catfish. An effective alternative to treat this bacterial infection is administering the probiotic Lactobacillus casei FNCC 0090. However, proper fisheries management is crucial for long-term success. The aim of this research is to determine the effect of administering the probiotic L. casei FNCC 0090 on the growth parameters and immune system of catfish. 200 catfish were divided into 5 different treatments in 5 replicates. The treatments were KN (negative control: without probiotic and infected), KP (positive control: without probiotic and not infected), A (5% probiotic and infected), B (10% probiotic and infected), C (probiotic 15% and infected). The density of probiotics administered is 108 CFU/ml. The fish were kept for 42 days; on the 35th day, the fish were infected with 1 x 108 CFU/ml A. hydrophila intramuscularly. The parameters observed in this study are fish growth (specific growth rate, SGR; feed conversion ratio, FCR; and survival rate, SR) and the immune system (phagocytic activity and the amount of lysozyme enzyme). The data obtained were analyzed with SPSS One Way ANOVA. The results showed that the administration of 15% probiotic L. casei FNCC 0090 had a significant effect on the growth parameters and immune system.